Who Guards the "Guardians of the System"? The Role of the Secretariat in WTO Dispute Settlement. Issue 3 (July 2022) - Pauwelyn, Joost; Pelc, Krzysztof
Abstract: For all the attention paid to the panelists and Appellate Body of the World Trade Organization (WTO), the Secretariat plays an overlooked and increasingly important role in the dispute settlement mechanism (DSM), including in selecting panelists, writing "issue papers" for adjudicators, providing economic expert advice, participating in internal deliberations, and drafting actual rulings. This Article argues that, given these functions, the DSM is better understood to be a sui generis administrative review process than it is a "World Trade Court."